Computational study of random boron-carbon-nitrogen systems - Nkambule, Sifiso Musa (My University, 2010)
Elastic properties, total formation energies and cell parameters of B-C structures are studied by molecular dynamics (MD) simulation. A well tested empirical Tersoff interatomic potentialfor simulation using a General Utility Lattice program (GULP). The results are compared with the available experimental results for Diamond and BC5. The work is extended to the study of B-C-N materials. We compare with available experimental results for BN and BC2N. The Bulk Modulus, Shear Modulus, Young’s Modulus and Elastic constants are obtained strongly implying hardness comparable to that of diamond. The Novel B-C and B-C-N material are proposed to be ultra-hard materials with different chemical and electrical properties from those of diamond and with potentially very useful application such as advanced abrasives, high temperature electronics and semiconductors.